2016
DOI: 10.2967/jnumed.115.168575
|View full text |Cite
|
Sign up to set email alerts
|

Left Ventricular Function Assessment Using 2 Different Cadmium-Zinc-Telluride Cameras Compared with a γ-Camera with Cardiofocal Collimators: Dynamic Cardiac Phantom Study and Clinical Validation

Abstract: This study compared two SPECT cameras with cadmium-zinc-telluride (CZT) detectors to a conventional Anger camera with cardiofocal collimators for the assessment of left ventricular (LV) function in a phantom and patients. Methods: A gated dynamic cardiac phantom was used. Eighteen acquisitions were processed on each CZT camera and the conventional camera. The total number of counts within a myocardial volume of interest varied from 0.25 kcts to 1.5 Mcts. Ejection fraction was set to 33%, 45%, or 60%. Volume, L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 34 publications
(39 reference statements)
1
11
0
1
Order By: Relevance
“…Imbert et al [21] reported the following classification of measured central spatial resolution: DNM 530c (6.7 mm) and DSPECT (8.6 mm). These results are concordant with previous findings by Bailliez et al [22] showing in both phantom and patients that LV volumes were higher using the DNM 530c model compared to DSPECT and to Anger camera equipped with cardiofocal collimators.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Imbert et al [21] reported the following classification of measured central spatial resolution: DNM 530c (6.7 mm) and DSPECT (8.6 mm). These results are concordant with previous findings by Bailliez et al [22] showing in both phantom and patients that LV volumes were higher using the DNM 530c model compared to DSPECT and to Anger camera equipped with cardiofocal collimators.…”
Section: Discussionsupporting
confidence: 93%
“…The phantom was filled under static equilibrium conditions at atmospheric pressure to provide a reproducible ejection fraction. Based on this equilibrium, ejection fraction was imposed by injecting a stroke volume into the ventricular cavity [15, 22]. As a consequence, true EDV and ESV were not known and thus could not be compared with measured volumes.…”
Section: Discussionmentioning
confidence: 99%
“…Simultaneous imaging of SPECT tracers labelled with different isotopes is feasible on the basis of the distinct gamma energies. However, because of crosstalk between energy spectra and scatter, non-trivial correction methods must be applied, and the energy resolution of scanners is continuously sought to improve this outcome 166,167 . Despite this limitation, dual-tracer SPECT imaging is feasible using 201 Tl or 111 In in healthy volunteers and in diverse disease settings, and including brain imaging, cardiac imaging and cancer imaging 166,[168][169][170][171] .…”
Section: Imaging Physiology In Patientsmentioning
confidence: 99%
“…Bailliez et al studied the impact of new CZT cameras on global and regional LV function assessment using phantom and patient data (10,11). In (10), LV volumes and EF measurements were compared using two CZT cameras (DNM 530c and D-SPECT) and a multipurpose camera equipped with multifocal collimators (IQ-SPECT, Siemens Healthcare).…”
Section: Respiratory Motion Correction In Mpimentioning
confidence: 99%